Assessing the acceptability, affordability, and availability of teleoncology services among cancer patients: A cross-sectional study - Praveen Suthar; Swati Kharbanda; Nitin Kumar Joshi; Komal Parmar; Parthasarathi Ganguly (Journal of Family Medicine and Primary Care)
Context: With the increasing burden of cancer and the need for continuous patient monitoring, teleoncology has emerged as an innovative approach to improve healthcare delivery. However, its utilization in real-world settings, particularly in resource-limited regions, remains underexplored. Aims: This study aims to assess cancer patients’ perceptions of teleoncology services, focusing on their acceptability, affordability, and accessibility. Settings and Design: A cross-sectional hospital-based study was carried out in Jaipur, Rajasthan. Methods and Material: This study was conducted from July 2024 to December 2024 using a semistructured questionnaire. Cancer patients utilizing teleoncology services for consultations, follow-ups, and disease monitoring were included. The Service User Technology Acceptability Questionnaire (SUTAQ) was used to measure acceptability. Data were analyzed for demographic variations and affordability perceptions. Statistical Analysis Used: Collected data were analyzed (Descriptive and Inferential) using SPSS V.25. Results: A total of 125 patients participated in the study, with a nearly equal gender distribution (50.79% male, 49.21% female). The mean age of male and female respondents was 48.27 ± 14.53 years and 43.17 ± 14.39 years, respectively. Acceptability: 77% of patients reported using teleoncology not just for cancer care but also for other health conditions. The mean satisfaction score was 4.2, indicating high acceptance. Affordability: There was no significant difference in perceptions of affordability across gender, geography, or age groups (P > 0.05). Patients found teleoncology cost-effective, with a mean affordability perception of 4.3 (agree to strongly agree). Availability: While 48.1% agreed that services were available 24/7, 38.4% disagreed, indicating gaps in accessibility. Specialist availability received a mean score of 3.6, reflecting moderate satisfaction. Conclusions: Teleoncology is widely accepted due to its convenience and affordability, but challenges remain regarding 24/7 service availability and digital literacy. A hybrid model integrating teleoncology with periodic in-person visits could enhance patient experience. Imminent research should focus on long-term outcomes and strategies to improve teleoncology adoption among underserved populations.